Effect of dietary fiber and threonine content on intestinal barrier function in pigs challenged with either systemic E. coli lipopolysaccharide or enteric Salmonella Typhimurium - Michael O. Wellington; Kimberley Hamonic; Jack E. C. Krone; John K. Htoo; Andrew G. Van Kessel; Daniel A. Columbus (Journal of Animal Science and Biotechnology, 2020)
Abstract Background The independent and interactive effects of dietary fiber (DF) and threonine (Thr) were investigated in growing pigs challenged with either systemic E. coli lipopolysaccharide (LPS) or enteric Salmonella Typhimurium (ST) to characterise their effect on intestinal barrier function. Results In experiment 1, intestinal barrier function was assessed via oral lactulose and mannitol (L:M) gavage and fecal mucin analysis in pigs challenged with E. coli LPS and fed low fiber (LF) or high fiber (HF) diets with graded dietary Thr. Urinary lactulose recovery and L:M ratio increased (P < 0.05) during the LPS inoculation period in LF fed pigs but not in HF fed pigs. Fecal mucin output was increased (P < 0.05) in pigs fed HF compared to LF fed pigs. In experiment 2, RT-qPCR, ileal morphology, digesta volatile fatty acid (VFA) content, and fecal mucin output were measured in Salmonella Typhimurium challenged pigs, fed LF or HF diets with standard or supplemented dietary Thr. Salmonella inoculation increased (P < 0.05) fecal mucin output compared to the unchallenged period. Supplemental Thr increased fecal mucin output in the HF-fed pigs (Fib × Thr; P < 0.05). Feeding HF increased (P < 0.05) VFA concentration in cecum and colon. No effect of either Thr or fiber on expression of gene markers was observed except a tendency (P = 0.06) for increased MUC2 expression with the HF diet. Feeding HF increased goblet cell numbers (P < 0.05). Conclusion Dietary fiber appears to improve barrier function through increased mucin production capacity (i.e., goblet cell numbers, MUC2 gene expression) and secretion (i.e., fecal mucin output). The lack of effect of dietary Thr in Salmonella-challenged pigs provides further evidence that mucin secretion in the gut is conserved and, therefore, Thr may be limiting for growth under conditions of increased mucin production.